Sociology in Iran: By Ali Akbar Mahdi and Abdolali Lahsaeizadeh. Bethesda, MD: Jahan Book Co., 1992, 141 pp. (American Journal of Islam and Society, 1993)
The book, with the help of empirical data, provides valuable informationabout the development of sociology as a discipline in Iran. It explains howthe discipline was introduced in one of the colleges of Tehran in 1946 andgradually, over a span of twenty-five years, became a popular subject ofteaching and research. The number of qualified students and staff is alsosteadily increasing. But more importantly, Iran now has a unifonn B.A.degree program consisting of 144 credit hours in eight 17-week semesters.Five categories of courses related to different areas and subareas are provided:general, base, main, elective, and specialized courses. In all of these courses,sociology and its various branches are mentioned.The M.A. degree program has been developed with the intention of preparinga competent cadre of future teachers for the higher centers of learning.The program is similar to that found in European and American universities,with the exception of courses on the social thought of Muslim thinkers andthe social ideas of Muslim philosophers, theologians, intellectuals, and historians.A doctoral program has also been introduced for training universityfaculty and researchers. The program requires thirty credit hours over a periodof seven semesters. Out of these credit hours, twenty-two are required courses ...